Design of a Circularly Polarized Planar Monopole Antenna with a Simplified Radiator Structure for UWB Applications - Park, Seungyong; Qu, Longyue; Park, Min-Seok; Jung, Kyung-Young (Journal of Electromagnetic Engineering and Science, 2024)
The demand for wideband circularly polarized (CP) antennas in wireless communication applications has been increasing, given that it offers reliable signals with reduced interference. In particular, planar monopole antennas are a popular choice for use in CP applications due to their compact size and ease of integration. However, achieving CP characteristics often requires complex modifications, an increased antenna size, and design complexity. To address these challenges, this study proposes a simplified radiator structure modification for CP planar monopole antennas and validates the performance of the proposed antenna for ultra-wideband (UWB) applications by conducting both frequency-domain and time-domain analyses. The size of the proposed antenna is 34 mm × 41 mm × 1.6 mm, with FR-4 as the substrate. Both the -10 dB S11 bandwidth and 6 dB axial ratio axial ratio is 3.46–5.5 GHz, with the radiation patterns in the frequency range of interest being omni-directional. The proposed UWB CP antenna also yields decent antenna performance in time-domain analyses, such as the antenna fidelity factor and the system fidelity factor.